Spinal muscular atrophy in the era of newborn screening: how the classification could change - Varone, Antonio; Esposito, Gabriella; Bitetti, Ilaria (Frontiers in Neurology, 2025)
Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disease caused by deletions or mutations in the Survival Motor Neuron 1 gene, associated with high morbidity and mortality related to muscle weakness. In recent years, the availability of new disease-modifying therapies and the extension of newborn screening has brought radical changes in the natural history of SMA at all ages. Historically, the classification of SMA has been based on age of onset and achievement of maximum motor milestone. In this new era, the historical classification of SMA by typology is no longer adequate to define the prognosis and type of SMA, nor to guide clinical management and treatment choice. The aim of this work is to discuss the current status of SMA neonatal screening and access to therapies across Europe and propose a new updated nomenclature, more suitable to guide clinicians in the management of SMA patients in the era of newborn screening. In this perspective, we evaluate and analyze the genetic basis of the disease, the current therapeutic landscape, the possible genotypic/phenotypic scenarios and the related clinical management.